Pengaruh Persepsi Harga, Kualitas Produk dan Word of Mouth Produk Skincare Scarlett Whitening Terhadap Keputusan Pembelian Konsumen di Kecamatan Tuah Madani Kota Pekanbaru - Aida Suryana; Ulfiah Novita (Yayasan Almanar Pujud, 2025)
Scarlett whitening is one of the local skincare brands founded in 2017. Scarlett whitening is produced by PT. Opto Lingkar Sejahtera, Indonesia. The purpose of this study was to determine the effect of price perception, product quality and word of mouth of Scarlett Whitening Skincare product on consumer purhasing decisions in Tuah Madani District, Pekanbaru City. The population in the study was the Tuah Madani District Community who used Scarlett Whitening Products. This type of research is quantitative research using the multiple linear regression method which was selected using the purposive sampling. The result of this study indicate the partially price perception, product quality and word of mouth have an effect on purchasing decisions. The results of the determination coefficient (R2) show that simultaneously the influence of the three independent variables on the dependent variable is 67.3% and the remaining 32.7% are other variables not examined in this study.